Perbandingan Kesejahteraan Antara Pengusaha dan Pegawai Perspektif Maqashid Syariah di Kelurahan Kejawan Putih Tambak Surabaya - Miyagi, Khea; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to identify and analyze Comparison Between Employers and Employees Welfare maqashid Shariah Perspective in the Village Kejawan Putih Tambak Surabaya. That is the basis of interview questions to determine the welfare comparison between employers and employees in terms of five aspects, namely, religion, life, intellect, lineage and property.This study used a qualitative approach with ethnographic strategy. Data was collected through interviews and direct observation to study the object. The analysis technique used is descriptive qualitative analysis narrate the results of interviews and direct observation.The results of this study is that there is little difference between employers and employee welfare. The welfare of employers better meet the criteria Maqashid Shariah Perspective. The employers have more time to gather with family, having time to pray in the mosque, pay more attention to their health and have more social activities than employees. While employees have limited time togather with family, can not pray in a timely manner, rarely have time to socialize and do not have time for a workout. Therefore employers mental welfare is better than employees.